DEVELOPMENT AND VALIDATION OF REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR GABAPENTIN AND ITS RELATED SUBSTANCES IN CAPSULE DOSAGE FORM AND EXCIPIENT COMPATIBILITY STUDIES - Patan, Afroz (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A simple, accurate, precise, and reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for gabapentin (GBP) and its related substances in the capsule dosage form and excipient compatibility studies. Methods: The review of literature indicates that various methods have been reported for the estimation of GBP. When some excipients were used for GBP, it produced degradation product called lactam due to the presence of more water content. Hence, a novel RP-HPLC method has been developed for studying excipient compatibility and related substances of GBP in capsule dosage form using excipients such as lactose anhydrous and dried maize starch which is having less water activity. Waters Alliance e2695 separation module with ultraviolet/photodiode array (UV/PDA) detector with Inertsil C8 (250 mmÃ—4.6 mm); 5 Î¼m with an injection volume of 50 Î¼l is injected and eluted with the (gradient program) mobile Phase A buffer: acetonitrile (940:60) and mobile phase B buffer: acetonitrile (700:300) pH 6.9 with 5 N potassium hydroxide which is pumped at a speed of 1.5 ml/min and detected by UV/PDA detector at 210 nm. The peaks of GBP and GBP-related compound A are well separated at 6.7 min and 34.5 min, respectively. Results: The method developed was approved for various parameters such as accuracy, specificity, precision, intermediate precision, range, linearity, robustness, limit of detection, limit of quantification, steadiness, and system suitability according to the International Conference on Harmonization guidelines. The results got were according to the acceptance criteria. Conclusion: The technique proposed was assured for detection of related substances in the marketed formulation and could be used for the routine analysis of GBP and GBP-related compound A in the capsule dosage form.